Using the service encounter model to enhance our understanding of business-to-consumer transactions in an electronic environment. - Massad, Nelson; Kevin Crowston (Proceedings of the 16th Bled eCommerce Conference, 2003)
The aim of this paper is to provide an alternative perspective to enhance our understanding of the transactions between customers and service providers in an electronic environment. The service encounter literature is well established in the Marketing field and provides an alternative model to explore online business-to-consumer transactions. The taxonomy of antecedents of satisfaction developed from this model has been tested over time, across respondents (i.e., customers’ perspective vs. employees’ perspective), and across different settings. This taxonomy, however, has been mostly restricted to the bricks-and-mortar environment. Based on the analysis of a pretest sample of customer-reported online experiences, the taxonomy has the potential to enhance our understanding of business-to-consumer online transactions. The next step is to carry out a complete study in order refine the taxonomy to account for the electronic context.
Keywords: E-commerce